DEVELOPMENT OF MANAGEMENT FOR ADMISSION OF NEW STUDENTS TO ISLAMIC BASED SCHOOLS USING THE PAID PROMOTE INSTAGRAM METHOD - Rafsanjani, Mohammad Fikri; Napisah, Nina; Latifah, Siti; Fasya, Nizar Muhammad; Badrudin, Badrudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study examines the role of Instagram, specifically through the paid promotion method, in managing student admissions (PPDB) in Islamic-based schools in West Java. Along with the development of information technology, social media, including Instagram, has become an effective promotional tool for educational institutions to increase visibility and appeal. Islamic-based schools in West Java have started to utilize this platform to attract the attention of parents and prospective students. However, many schools need help using Instagram as a promotional medium due to budget limitations and a lack of in-depth understanding of managing advertising campaigns. This research aims to identify the benefits and challenges faced and evaluate the effectiveness of using paid promotion on Instagram to strengthen branding and increase student enrollment. This study is expected to provide insights for schools in optimizing their promotional strategies using social media to support the success of PPDB management in the future.